Using the Government Finance Statistics Manual 2001 (GFSM 2001) Statistical Framework to Strengthen Fiscal Analysis in the Fund. (Policy Papers; Policy Paper, 2005)
This paper responds to the Board's call for greater consistency in fiscal reporting in line with GFSM 2001. In this context, the paper summarizes the framework, reviews the implementation process of the GFSM 2001 framework by member countries and Fund staff, and proposes pilot studies. It seeks the support of the Board for gradual adoption of the framework as the basis for fiscal analysis in Fund staff reports.